Strategy Implementation to Improve Human Quality Resources in Business Plan over LH Hotel - Helmy Nur Efendi Yusuf; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Penerbit Kemala Indonesia, 2019)
Hotel is an accommodation service business to bring a service, comfortable, and lodging facilities needed for those who want lodging facilities for the benefit of family, vacation or on job. This business is related to facilitate a people as customers, so this business is related to service quality. Quality of service is very determining by success factor of this business. Service quality is a form of consumer assessment in the level of service received with the expected level of service. The success of a company's operations is determined by many factors, one of which is the employee. Employees are people who deal directly with customers. In addition to hotel buildings which include design and layout, employees also become important assessments for customers. Therefore, training and developing employees in a service business is important to achieve company goals.